Orphanage tourism and orphanage volunteering: implications for children - van Doore, Kathryn E.; Nhep, Rebecca (Frontiers in Sustainable Tourism, 2023)
Orphanage tourism refers to visits or volunteering in orphanages as part of a holiday or tourist experience. Orphanage tourism is a consumer product which represents the intersection of the desire of orphanage operators to gain access to international funding and the desire of tourists and volunteers to give back to less developed countries. Despite its popularity amongst tourists and volunteers, orphanage tourism has come under increasing scrutiny and criticism for its impacts on child rights, development, and the role it plays in driving the unnecessary institutionalization of children, child trafficking and exploitation in residential care settings. This article outlines differing perspectives on orphanage tourism and volunteering from the last decade of research. It examines the contexts in which orphanage tourism occurs and outlines the drivers for this form of tourism. In addition, it discusses the implications of orphanage tourism for children including impacts on child agency, child rights, child development, child protection, and child trafficking and exploitation. We conclude that the limited benefits for children involved in orphanage tourism are outweighed by child protection concerns coupled with negative impacts on child agency, rights, and development.